Predictors of Learning Satisfaction in Japanese Online Distance Learners - Bray, Eric; Aoki, Kumiko; Dlugosh, Larry (International Review of Research in Open and Distributed Learning, 2008)
Japanese distance education has been slow to utilize the Internet, and mainly depends on the mail system and to a lesser extent TV broadcasting as its mode of delivery. However, since 2001 regulations have been relaxed to allow students to complete all course requirements for a university degree via online distance learning. This paper reports the results of a questionnaire study administered to the students (N=424) enrolled in one of Japan’s few online distance universities. Satisfaction with learning was explored by examining student opinions and learning preferences in regard to five aspects of distance learning identified as important: 1) teacher interaction, 2) content interaction, 3) student interaction, 4) computer interaction and 5) student autonomy. In addition, student responses to three open-ended questions were included in the analysis. The results indicated students were generally satisfied with their learning, and that specifically, learning satisfaction was higher for students who: 1) could persevere in the face of distance learning challenges, 2) found computers easy to use, 3) found it easy to interact with instructors, and 4) did not prefer social interaction with others when learning.